Effect of TGF-β3 on wound healing of bone cell monolayer in static and hydrodynamic shear stress conditions - Al-Attar, Hawra; Damiati, Laila A.; Keshel, Saeed Heidari; Tuinea-Bobe, Cristina; Damiati, Samar; Saeinasab, Morvarid; Sefat, Farshid (Frontiers in Medicine, 2024)
Wound healing is characterized as a complicated and sophisticated biological process through which tissue heals and repairs itself after injury. However, the normal wound healing process relies on different growth factors as well as the presence of an accurate cytokine level to ensure appropriate cellular responses. In the case of wound healing, the effects of various growth factors have been studied, but the effects of transforming growth factor beta (TGF-β) on wound healing have been found to be more significant because of its broad spectrum of impacts on healing the wounded tissues or skins. In the current study, the impact of TGF-β3 in bone cells' wound healing was examined in vitro. Furthermore, the activities and characteristics of TGF-β3, as well as those of related growth factors throughout this wound healing process, were studied under hydrodynamic shear stress conditions as well as static conditions of cultured bone cells. We demonstrated that a positive outcome of TGF-β3 treatment was found after 24 hours under a static condition, while TGF-β3 treatment was found to be effective under a dynamic condition for wound closure. In the case of the dynamic condition, a full wound closure was obtained after 18 hours in both the control and TGF-β3 treatment, while in the case of static conditions, wounds were found to remain open, even after 24 hours, for both the control and TGF-β3 treatment. Additionally, in the static condition, the wound closure rate with TGF-β3 treatment was found to be quicker than that of the control flask, which implies that wound healing can be postponed in the static condition. In the dynamic condition, the wound healing process became more rapid in a cultured cell environment.To conclude, the synergistic effect of TGF-β3 and hydrodynamic shear stress conditions had a positive impact on increasing wound healing and improving the rate of wound closure.